Bromophenol concentrations in fish from Salvador, BA, Brazil - Oliveira,Aline S. (2009)
The main objective of this work is to evaluate the occurrence of bromophenols (2bromophenol, 4bromophenol, 2,4dibromophenol, 2,6dibromophenol and 2,4,6tribromophenol), in the flesh and guts in two species of the LutjanidaeFamily: Lutjanus synagris and Ocyurus chrysurus. The bromophenols were extracted by steam distillation with pentaneether (7:3 v/v), identified by reverse phase High Performance Liquid Chromatography (HPLCUV), and quantified bythe externalstandard method. Total bromophenol concentrations were similar in the muscle of both species, rangingfrom 36 ng g¹ to 349 ng g¹. The total bromophenol concentrations in stomach (ranging from 12 ng g¹ to 586 ng g¹)were slightly higher than in muscle. The presence of bromophenol in the muscles of the species under study may occuras a result of their diet. The results of this work are therefore expected to contribute toward a better understanding ofthe path of bromophenol absorption from the fish's stomach to the rest of its body.